Reconstructing 'Dropout' : A Critical Ethnography of the Dynamics of Black Students' Disengagement from School - Dei, George J. Sefa (George Jerry Sefa), 1954- (Book collections on Project MUSE., 1997)
"Based on a three-year study in the greater Toronto area, Reconstructing 'Drop-out' establishes a new frame of reference for understanding the drop-out dilemma. It is a call for social action and transformation that should not be ignored by researchers, teachers, administrators, and the Black community at large."--Jacket